Nieuwsbrief OudRoze : nieuws en informatie over 'roze' wonen, zorg en welzijn. (Amsterdam : Oud Roze.)
Fonds Suzan Daniel (FSD)
Periodiciteit: driemaandelijks
Redactie: Vinkenstraat 185, 1013 JR Amsterdam
Nederlands
Periodiek